2000
DOI: 10.1590/s1415-43662000000100013
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la actividad biologica de dos suelos de los tableros costeros del NE de Brasil enmendados con residuos agricolas: vinaza y torta de canã de azúcar

Abstract: RESUMENSe han seleccionado los epipediones de dos suelos representativos de la zona de Tableros Costeros de Brasil, dedicados mayoritariamente al monocultivo de la caña de azúcar. Estos fueron enmendados con torta de caña de azúcar (T), de relación C/N = 19,33, en dosis de 10, 20 y 30 t ha -1 , (T 1 , T 2 y T 3 ), respectivamente; la enmienda con vinaza de caña (V), de relación C/N = 32,17, fue de 30, 60 y 90 m 3 ha -1 , (V 1 , V 2 y V 3 ), respectivamente. Dichas enmiendas se incorporanon al suelo sin compost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Estimula la formación de agregados, roots of sugarcane, the exploration area of the roots, stem diameter and the absorption of nitrogen and potassium (Villanueva et al 1998). Also, Tenorio et al (2000) found high rates of mineralization with sugarcane sludge doses (10 and 20 t ha -1 ) and in the case of the application of vinasse as mineralization rate was found in the dose 30 m 3 ha -1 . In none of these the biological activities were inhibited by adding the amendments directly without composting.…”
Section: Conclusionesmentioning
confidence: 82%
See 1 more Smart Citation
“…Estimula la formación de agregados, roots of sugarcane, the exploration area of the roots, stem diameter and the absorption of nitrogen and potassium (Villanueva et al 1998). Also, Tenorio et al (2000) found high rates of mineralization with sugarcane sludge doses (10 and 20 t ha -1 ) and in the case of the application of vinasse as mineralization rate was found in the dose 30 m 3 ha -1 . In none of these the biological activities were inhibited by adding the amendments directly without composting.…”
Section: Conclusionesmentioning
confidence: 82%
“…Algunos efectos después de aplicar cachaza y vinazas son que la cachaza favorece el número y longitud de las raíces de la caña de azúcar, el área de exploración de la raíz, diámetro del tallo y la absorción de nitrógeno y potasio (Villanueva et al 1998). Asimismo, Tenorio et al (2000) encontraron tasas de mineralización alta con dosis de cachaza (10 y 20 t ha -1 ) y en el caso de la aplicación de vinaza la mayor tasa de mineralización se encontró en la dosis con 30 m 3 ha -1 . En ninguno de los casos anteriores se inhibió la actividad biológica al añadir las enmiendas directamente sin previo compostaje.…”
Section: Efecto Sobre Las Características Biológicas Del Suelounclassified
“…Information about the use of vinasse for pathogenic agents control are quite scarce, although it is known that the vinasse increases the biological activity in the soil, which favors potential antagonistic microorganisms, as well as promotes the organic substances formation, such as volatile fatty acids, which may have nematicide action (Tenório et al, 2000). Therefore, the objective of this study was to evaluate the vinasse effect applied to the soil in the control of P. brachyurus in soybean crop.…”
Section: Introductionmentioning
confidence: 99%